Measles seroprevalence in persons over one year of age in Chandigarh, India - Joseph L. Mathew; Dakota Riopelle; R K Ratho; Bhavneet Bharti; Mini P. Singh; Vikas Suri; Bradley F. Carlson; Abram L. Wagner; Matthew L. Boulton (Taylor & Francis Group, 2022)
Measles continues to result in focal outbreaks in India, despite over three decades of universal infant vaccination. The aims of this study were to examine measles immunity in the population of Chandigarh, India, and to compare immunity by vaccination vs. natural infection. In a cross-sectional study of individuals 1-60 years selected from 30 communities within Chandigarh during 2017-2018, measles immunity was assessed using serological surveys. Seropositivity was compared across demographic groups, and by prior history of vaccination and natural history of infection. Among those 1-20 years old, measles seropositivity, and histories of measles vaccination or prior measles diagnosis were separately assessed as outcomes in logistic regression models, with demographic factors as independent variables. Among 1690 participants, 94% were seropositive, and 6% had borderline or negative antibody levels. Of those positive, 30% had prior vaccination, 16% had a history of natural infection, and 54% had an unknown history. Over 50% of individuals among those >20 years old, had unknown history of immunity. In the multivariable regression models, vaccination was more common in younger ages (P < .0001), and in males compared to females (P = .0220), and in those with more education (P < .0001). The majority of the population was seropositive, and seropositivity increased with age. Older age groups were more likely to be protected because of previous natural infection, whereas younger age groups were protected by vaccination. There was inequity in vaccination coverage by gender, and maternal education status.